Gerakan Messianisme Di Indonesia Masa Kolonial: Sebuah Tinjauan Teoritis - Panis Dhbi Salam (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2018)
Not all the ideal concepts of the ratu adil movements, such as millenarism, messianism, nativism, holy war or magical mysticism, emerged in puputan wars and koreri movements. In puputan wars, the symptoms of nativisme as the desire to restore the glory of Bali which was existed in the past when the kingdom of Bali untouched by foreign influences appeared. Furthermore, in Koreri movements which was wrapped up by the spirit of messianism and millenarism, the symptoms of nativism also strongly appeared. Koreri movements is actually a form of “ceremonial reception” to the glorious past that had suffered a discontinuities of history.